The Tender Auction System: Secure Transactions for Goods and Services - Fangki, Rachman (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2024)
This study examines the development and implementation of a tender auction system designed to enhance the security, transparency, and efficiency of procurement processes. The shift from traditional paper-based tendering to electronic platforms has introduced both opportunities and challenges, particularly concerning transaction security. The research highlights the need for robust security measures to safeguard against fraud, data breaches, and other vulnerabilities that could compromise the integrity of the tendering process. Through a structured approach involving problem identification, literature review, system design, and rigorous testing, the study successfully develops a tender auction system that ensures secure transactions. The system’s functionality, including user authentication, data management, and reporting, was validated through blackbox testing, confirming its reliability. The findings underscore the system's effectiveness in maintaining secure and transparent procurement processes, contributing to greater trust among stakeholders.